2015
DOI: 10.1016/j.neurobiolaging.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone ameliorates tau pathology and cognitive decline via restoration of glial glutamate transporter in a mouse model of Alzheimer's disease

Abstract: TauAmyloid b a b s t r a c t Glial glutamate transporter, GLT-1, is the major Na þ -driven glutamate transporter to control glutamate levels in synapses and prevent glutamate-induced excitotoxicity implicated in neurodegenerative disorders including Alzheimer's disease (AD). Significant functional loss of GLT-1 has been reported to correlate well with synaptic degeneration and severity of cognitive impairment among AD patients, yet the underlying molecular mechanism and its pathological consequence in AD are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 56 publications
7
110
0
1
Order By: Relevance
“…Moreover, studies of a heterozygous GLT-1 knockdown in an AD mouse model showed exacerbated cognitive decline further supporting the theory that dysfunction of the astrocyte glutamate transporter is involved in AD pathogenesis3031. Recent in vitro results suggest that Aβ species are responsible for the loss of GLT-1 expression as a part of their toxicity to astrocytes32. Therefore, we treated APPPS1 mice with ceftriaxone to determine whether GLT-1 expression and/or transporter activity could be upregulated around plaques and whether this would restore normal glutamate dynamics in this region.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, studies of a heterozygous GLT-1 knockdown in an AD mouse model showed exacerbated cognitive decline further supporting the theory that dysfunction of the astrocyte glutamate transporter is involved in AD pathogenesis3031. Recent in vitro results suggest that Aβ species are responsible for the loss of GLT-1 expression as a part of their toxicity to astrocytes32. Therefore, we treated APPPS1 mice with ceftriaxone to determine whether GLT-1 expression and/or transporter activity could be upregulated around plaques and whether this would restore normal glutamate dynamics in this region.…”
mentioning
confidence: 66%
“…This comparison indicates that the changes are very region specific and subtle and will be lost if not analysed with the necessary spatial resolution. Interestingly, Zumkehr et al 32. conducted behavioural tests in 3xTg-AD mice after ceftriaxone treatment of 2 months and found a significant cognitive improvement in the Morris water maze and novel object recognition tests.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, soluble Aβ oligomers were proved to be capable of inducing glutamate release from astrocytes [121]. The downregulation of the expression of excitatory amino acid transporter 2, one of the transporters responsible for glutamate uptake by astrocytes, was demonstrated in transgenic mouse models as well [122,123]. However, the available data on human specimens with regard to this issue are controversial [124][125][126][127].…”
Section: Glutamate Excitotoxicity In Alzheimer's Diseasementioning
confidence: 99%
“…As these authors noted, this implies that ceftriaxone could have therapeutic activity in a range of neurodegenerative conditions, essentially the examples we discussed earlier as exhibiting excitotoxicity. With this mechanism in mind, ceftriaxone is nowadays under active consideration as a therapy in models of AD [235], stroke [236], TBI [237239], and PD [240243]. The most complete evidence consistent with this approach to date is a very recent extensive report on ceftriaxone rescuing brain function in Toxoplasma gondii -infected mice [244].…”
Section: Agents That Do Not Influence Tnf But Still Reduce Extracellumentioning
confidence: 99%